Frequency of Second Mesiobuccal Canals in Maxillary First Molar using Cone Beam Computed Tomography in Libyan Subpopulation in Zliten city - Aalaali Ehbesh; Mohamed Attir; Ahmed Alteer (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was conducted to evaluate the frequency of Second Mesiobuccal Canals (MB2) in maxillary first molar teeth of a Libyan subpopulation in Zliten city, and to assess the presence of MB2 based on gender and location using Cone Beam Computed Tomography. The study was a retrospective study done by screening 764 CBCT (X-MIND Prime®3D – Acteon software), with patients being came routinely to Al-Tasneem Private Dental Ploy-clinic in Zliten city during the period from July 2023 until June 2024. Two hundred seventy-three teeth of this study (62.6%) were female; whereas 163 (37.4%) were male. About 48% of these maxillaries first molar teeth were right, while 52% were left teeth. The age of patients in present study were between 13 and 84 years old. The frequency of MB2 of maxillary first molar in Libyan subpopulation in Zliten city were 77.5%. Although there was no significant statical differences in frequency of MB2 between the male and female; the occurrence of MB2 in maxillary first molar teeth were higher in male with (80.4%) than in female with (75.8%). In the current study although there was no significant statical differences in frequency of MB2 between the left and right occurrence of MB2 of maxillary first molar, which was slightly higher in the left side with (51.77%) than the right side with (48.22%). The incidences of MB2 in maxillary first molar teeth of a Libyan subpopulation in Zliten city were 77.5%. The three separated roots were in 100% of teeth. The frequency of MB2 in male was greater on the right side compared with the left, whereas incidences of MB2 in female were higher in the left side than the right side. The age group of 21-40 years old had the greatest rates of MB2 أجريت هذه الدراسة لتقييم نسبة تكرار القنوات الدهليزية المتوسطة الثانية في الضرس الأول في الفك العلوي لفئة فرعية من السكان الليبيين في مدينة زليتن، وتقييم وجود القنوات الدهليزية المتوسطة الثانية بناءً على الجنس وموقع السن باستخدام التصوير المقطعي المخروطي الشعاعي. كانت الدراسة دراسة استرجاعية أجريت من خلال فحص 764 CBCT (X-MIND Prime®3D - برنامج Acteon)، مع المرضى الذين يأتون بشكل روتيني إلى عيادة التسنيم الخاصة لطب الأسنان في مدينة زليتن خلال الفترة من يوليو 2023 حتى يونيو 2024. كانت مائتان وثلاثة وسبعون سنًا في هذه الدراسة (62.6٪) من الإناث؛ بينما كان 163 (37.4٪) من الذكور. حوالي 48٪ من هذه الضروس الأولى العلوية كانت يمنى، بينما كانت 52٪ من الأسنان اليسرى. تراوحت أعمار المرضى في الدراسة الحالية بين 13 و 84 عامًا. كان معدل حدوث القنوات الدهليزية المتوسطة الثانية في الضروس الأولى العلوية في السكان الليبيين في مدينة زليتن 77.5٪. وعلى الرغم من عدم وجود فروق إحصائية كبيرة في معدل حدوث القنوات الدهليزية المتوسطة الثانية بين الذكور والإناث؛ إلا أن حدوث القنوات الدهليزية المتوسطة الثانية في الضروس الأولى العلوية كان أعلى عند الذكور بنسبة (80.4٪) منه عند الإناث بنسبة (75.8٪). في الدراسة الحالية، على الرغم من عدم وجود فروق إحصائية كبيرة في تكرار حدوث القنوات الدهليزية المتوسطة الثانية بين حدوث القنوات الدهليزية المتوسطة الثانية في الضرس الأول العلوي الأيسر والأيمن، والذي كان أعلى قليلاً في الجانب الأيسر بنسبة (51.77٪) من الجانب الأيمن بنسبة (48.22٪). بلغت حالات القنوات الدهليزية المتوسطة الثانية في الضرس الأول العلوي لدى مجموعة فرعية ليبية في مدينة زليتن 77.5٪. كانت الجذور الثلاثة المنفصلة في 100٪ من الأسنان. كان تكرار القنوات الدهليزية المتوسطة الثانية لدى الذكور أعلى في الجانب الأيمن مقارنة باليسار، في حين كانت حالات القنوات الدهليزية المتوسطة الثانية لدى الإناث أعلى في الجانب الأيسر من الجانب الأيمن. كانت الفئة العمرية 21-40 عامًا لديها أعلى معدلات القنوات الدهليزية المتوسطة الثانية